FINDING A LOGICAL DATA-DRIVEN PROCESS FOR QUANTIFICATION OF OPERATION PHASE CO2 EMISSION FROM URBAN RESIDENTIAL BUILDINGS - Bose, Sumit; Roy, Madhumita (International Journal of Engineering Science Technologies, 2025)
The building sector is found to be one of the biggest consumers of energy and emitter of GHG gases. Considering the whole life-cycle of the building, the ‘operation phase’ constitutes most of the emission. With a goal to investigate the quantitative and qualitative parameters of Household Carbon Footprint, this paper sets research boundaries as study of CO2 emission from the operation phase of a multi-storied and multi-tenement residential building in the urban area of Newtown, beside Kolkata, in India. The aims of the study are - 1) identification of causes or sources of emission in a residential building and 2) finding a logical and scientific strategy and method for quantification of CO2 emitted. The sources of emission from residential buildings are identified as – electricity usage, fuel (LPG) usage for cooking, fuel (Petrol) usage for vehicle idling time inside the building premises, respiration by residents and potable water consumption. Study of existing literature shows that there are gaps in research methods and end results due to wide variations in selection of sources of emission, application of different methods for quantification and choice of different coefficients of CO2 emission and related factors by different agencies and research papers. This paper searches for coefficients, factors and standards which are more local, recent and apt and tries to find exact application of such energy by end-users. The quantification results show that approximately 59.88% of the total CO2 emission from a multi-storied multi-tenement urban residential building is from consumption of electricity, 20.49% from respiration, 10.27% from consumption of LPG for cooking, 5.36% from water consumption and lastly 3.99% from petrol consumption by automobiles owned by the residents.